Analisis Lingkungan Pengendapan dan Sistem Petroleum berdasarkan Integrasi Data Seismik dan Sumur di Pesisir Cekungan Sumatra Tengah: Analysis of Depositional Environment and Petroleum System based on Integration of Seismic and Well Data in the Coastal of Central Sumatra Basin (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
As one of the hydrocarbon-producing basins in Indonesia, the Central Sumatra Basin’s development had been hampered due to limited exploration and studies. This study aimed to identify depositional environments and petroleum systems through stratigraphic seismic and well studies. This study used a seismic method with Hampson Russell and Petrel software. Log data helped process seismic data with Interactive Petrophysic (IP) software and Techlog for well data processing. This research zone had five depositional sequences, most of which were formed in the depositional environment of branching channels and estuaries. There were two potential source rocks, namely in the Pematang Formation and shale layers in the upper TST-1. Based on stratigraphic sequence analysis on seismic sections, petroleum systems were identified in the Merak, Melibur, and Garib wells on the coast of the Central Sumatra Basin. Hydrocarbon reservoirs were found in the Bekasi, Bangko, and Menggala Formations and parts of the Pematang Formation; source rock was found in parts of the Menggala and Pematang Formations. The determination of reservoir layers and source rock was strengthened by the results of the analysis of wells located on seismic trajectories. Faults were useful as migration pathways for hydrocarbon fluids from source rock to reservoirs so that a petroleum system was formed in the area. This layer had immature and mature parent rocks. It was concluded that the depositional environment and the petroleum system in the wells in the area could be identified.